Perioperative outcomes after radical cystectomy at NCI-designated centres: Are they any better? - Roghmann, Florian (Can Urol Assoc J, 2015)
INTRODUCTION: In 1971, the National Cancer Institute (NCI) introduced a network of NCI-designated Cancer Centers (CC), which underwent a comprehensive approval process relying on research, education and prevention activities. In this study, we examine the effect of CC status on perioperative outcomes after radical cystectomy (RC). METHODS: Within the Nationwide Inpatient Sample, we focused on RC performed from 2006 to 2010. As all recognized centres were residency teaching institutions, we stratified according to teaching and CC-teaching status. We examined the rates of in-hospital mortality, intra- and postoperative complications, prolonged length of hospital stay, as well as blood transfusion. Multivariable logistic regression analyses were further adjusted for confounding factors. RESULTS: Overall, 22 840 RC patients (5451 at non-teaching, 10 857 at residency teaching, 6532 at CC-teaching institutions) were identified. Patients treated at residency teaching and CC-teaching institutions were younger, had less comorbidities, and more likely to have private insurance. In multivariable analyses, patients treated at residency and CC-teaching institutions were less likely to experience postoperative complications (odds ratio [OR] 0.73 and 0.66, respectively) and blood transfusions (OR 0.77 and 0.53, respectively) relative to patients treated at non-teaching institutions. In addition, CC patients were also less likely to experience in-hospital mortality (OR 0.61, all p < 0.001) as compared to non-teaching institutions. CONCLUSIONS: On average, patients treated at residency and CC-teaching institutions are less likely to experience unfavourable outcomes after RC. Moreover, patients treated at CC fared better than patients treated at residency teaching institutions. Our findings acknowledge the quality of RC care at accredited centres.